The Role of Physical Activity for Early Childhood - Maria, Ilga; Masfufah, Zia Zalzilah (Jayapangus Press, 2025)
In industrial revolution, social skills is an important thing that can sustain our life. Education is one of the ways that can take early as an investment in social skills in order to achieve cognitive and a better life in the future. Such social skills can be developed even enhanced through physical activity. But in developing countries one of them is Indonesia, shows data that physical activity is not an urgency in early childhood education. Parents or educators more focus on the children's cognitive abilities for formal school preparation. The study aims to describe the importance of physical activity in developing the social skills of young children. The study are used qualitative methods with a literary review technique. The results of this study found that physical activity is highly influential and is important in developing, as well as in improving children's social skills. Through physical activity, children become more able to explore a variety of things, actualize more broadly, express their emotions, and gain new knowledge through grit study. It can affect both cognitive ability and a child's life over a longer period of time in the future.